Effect of the addition of osmotic dilators to medical induction of labor abortion: A before-and-after study. (January 2020) - Bertholdt, Charline; David, Manuel Gomes; Gabriel, Priscillia; Morel, Olivier; Perdriolle-Galet, E.
Abstract: Objectives: The main objective of this study was to assess the induction-to-delivery interval with or without the use of osmotic dilators for induced abortion. As secondary objectives, women outcomes were assessed. Study design: This retrospective single-center observational before and after study reviewed records from a university hospital maternity unit from 2002 through 2016 and included all women undergoing abortion for medical reasons at and after 14 weeks of gestation. Two groups were compared: group "no dilators", which used first misoprostol without dilators, and group "dilators", which used osmotic dilators before misoprostol administration. The main outcome was the induction-to-delivery interval. Results: The study included 491 women: 383 in group "no dilators" and 108 in group "dilators". The induction–delivery interval was significantly lower in the group "dilators" compared to "no dilators" (427.7 min vs 639.7 min, P  < 0.001), as was the cumulative misoprostol dose (990 μg vs 1449 μg, P  < 0.001). The delivery rate within 6 h was significantly higher in the "dilators" group compared to "no dilators" group (50.0% vs 29.8%, P  = 0.002). Conclusion: The use of osmotic dilators for cervical ripening before administration of misoprostol for induced abortion appears to be effective in reducing the induction-delivery interval.